Exploring ionic liquid-laden metal-organic framework composite materials as hybrid electrolytes in metal (ion) batteries - Urgoiti-Rodriguez, Maitane; Vaquero-Vílchez, Saloa; Mirandona-Olaeta, Alexander; Fernández de Luis, Roberto; Goikolea, Eider; Costa, Carlos M.; Lanceros-Mendez, Senentxu; Fidalgo-Marijuan, Arkaitz; Ruiz de Larramendi, Idoia (Frontiers in Chemistry, 2022)
This review focuses on the combination of metal-organic frameworks (MOFs) and ionic liquids (ILs) to obtain composite materials to be used as solid electrolytes in metal-ion battery applications. Benefiting from the controllable chemical composition, tunable pore structure and surface functionality, MOFs offer great opportunities for synthesizing high-performance electrolytes. Moreover, the encapsulation of ILs into porous materials can provide environmentally benign solid-state electrolytes for electrochemical devices. Due to the versatility of MOF-based materials, in this review we also explore their use as anodes and cathodes in Li- and Na-ion batteries. Finally, solid IL@MOF electrolytes and their implementation into Li and Na batteries have been analyzed, as well as the design and advanced manufacturing of solid IL@MOF electrolytes embedded on polymeric matrices.